The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1016/j.dcn.2015.10.009
|View full text |Cite
|
Sign up to set email alerts
|

Selective attention neutralizes the adverse effects of low socioeconomic status on memory in 9-month-old infants

Abstract: Socioeconomic status (SES) has a documented impact on brain and cognitive development. We demonstrate that engaging spatial selective attention mechanisms may counteract this negative influence of impoverished environments on early learning. We previously used a spatial cueing task to compare target object encoding in the context of basic orienting (“facilitation”) versus a spatial selective attention orienting mechanism that engages distractor suppression (“IOR”). This work showed that object encoding in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 53 publications
(18 citation statements)
references
References 45 publications
2
15
0
Order By: Relevance
“…Of greater interest was the pattern of SES disparities across the different neurocognitive systems tested; it was uneven, as demonstrated by statistically significant SES 3 system interactions in each study, with language, executive function (especially working memory and cognitive control), and declarative memory the most strongly related to SES. Other studies, focused on single systems, are generally in accord with these results, finding language (Fernald et al, 2013;Hart and Risley, 1995;Hoff, 2013), executive function (EF; Lawson et al, 2017b;Raver et al, 2013;Turrell et al, 2002), and memory ability varying with SES (Fuhrer et al, 1999;Noble et al, 2015b;Hermann and Guadagno, 1997;Markant et al, 2016). Functional Correlates of SES in the Healthy Human Brain The behavioral findings suggest that we should expect to find SES correlations with more direct measures of brain function, such as fMRI or event-related potential (ERP), and this has indeed been the case in a small but growing part of the literature.…”
Section: Behavioral Correlates Of Ses For Specific Neurocognitive Syssupporting
confidence: 52%
“…Of greater interest was the pattern of SES disparities across the different neurocognitive systems tested; it was uneven, as demonstrated by statistically significant SES 3 system interactions in each study, with language, executive function (especially working memory and cognitive control), and declarative memory the most strongly related to SES. Other studies, focused on single systems, are generally in accord with these results, finding language (Fernald et al, 2013;Hart and Risley, 1995;Hoff, 2013), executive function (EF; Lawson et al, 2017b;Raver et al, 2013;Turrell et al, 2002), and memory ability varying with SES (Fuhrer et al, 1999;Noble et al, 2015b;Hermann and Guadagno, 1997;Markant et al, 2016). Functional Correlates of SES in the Healthy Human Brain The behavioral findings suggest that we should expect to find SES correlations with more direct measures of brain function, such as fMRI or event-related potential (ERP), and this has indeed been the case in a small but growing part of the literature.…”
Section: Behavioral Correlates Of Ses For Specific Neurocognitive Syssupporting
confidence: 52%
“…Previous research demonstrated that attention orienting mechanisms interacted with IQ to predict recognition memory among children and adolescents (Markant & Amso, 2014) and with parental socioeconomic status (SES) to predict recognition memory among 9-month-old infants (Markant, Ackerman, Nussenbaum, & Amso, under review). Specifically, IQ was the only predictor of recognition memory among children who engaged facilitation-based orienting during encoding.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, SES predicted infants’ recognition memory when they engaged in facilitation-based orienting during encoding, with infants from lower SES environments showing poorer recognition memory relative to those from high SES environments. However, this effect of SES was mitigated when infants engaged in IOR-based orienting during encoding, as infants from low SES environments performed at the same level as those from high SES environments (Markant et al, under review). The present data indicating that infants’ prior pet experience influences learning in the context of facilitation-based orienting but not IOR-based orienting replicates this pattern and suggests that selective attention functions as a robust online learning mechanism during visual exploration.…”
Section: Discussionmentioning
confidence: 99%
“…Although reciprocal connections exist between the PFC and both the ventral and dorsal visual streams, existing evidence supports the notion that variation in environmental experience is associated with development of the ventral visual stream and associated functions (see Table 1). For example, a series of recent behavioral studies suggest that SES influences ventral visual stream-dependent processes, including object-based attention (Amso et al, 2014), but not dorsal visual stream-dependent processes, including spatial attention (Markant et al, 2016). Furthermore, SES is positively associated with both feature-based attention for color and object-based attention, processes that are dependent on ventral visual stream function; in contrast, SES is unrelated to attention to motion, which is processed in the dorsal visual stream (Werchan et al, 2019) and disparities in focused attention between high- and low-SES infants emerge as object complexity increases (Clearfield and Jedd, 2012).…”
Section: Ses-related Differences In the Ventral Versus Dorsal Visual mentioning
confidence: 99%